2007
DOI: 10.1021/ja073977d
|View full text |Cite
|
Sign up to set email alerts
|

Confinement or the Nature of the Interface? Dynamics of Nanoscopic Water

Abstract: The dynamics of water confined in two different types of reverse micelles are studied using ultrafast infrared pump-probe spectroscopy of the hydroxyl OD stretch of HOD in H2O. Reverse micelles of the surfactant Aerosol-OT (ionic head group) in isooctane and the surfactant Igepal CO 520 (nonionic head group) in 50/50 wt % cyclohexane/hexane are prepared to have the same diameter water nanopools. Measurements of the IR spectra and vibrational lifetimes show that the identity of the surfactant head groups affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
312
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(345 citation statements)
references
References 80 publications
26
312
3
4
Order By: Relevance
“…We can observe that t values obtained from computer simulations of unconstrained bulk TIP3P water 23 are markedly smaller than those reported here. This would confirm that the micellar confinement tends to slow down orientational correlations, in line with that suggested by the non-linear IR experiments of Piletic et al 8,24 or by Dokter et al, 7 who employed mid-infrared ultrafast pump-probe spectroscopy for several classes of reverse micelles. Moreover, note also that the previous observed trends are significantly enhanced as one singles out exclusively the contributions from interfacial water.…”
Section: Reorientational Motions and Diffusive Behavior Of Pure Watersupporting
confidence: 86%
See 1 more Smart Citation
“…We can observe that t values obtained from computer simulations of unconstrained bulk TIP3P water 23 are markedly smaller than those reported here. This would confirm that the micellar confinement tends to slow down orientational correlations, in line with that suggested by the non-linear IR experiments of Piletic et al 8,24 or by Dokter et al, 7 who employed mid-infrared ultrafast pump-probe spectroscopy for several classes of reverse micelles. Moreover, note also that the previous observed trends are significantly enhanced as one singles out exclusively the contributions from interfacial water.…”
Section: Reorientational Motions and Diffusive Behavior Of Pure Watersupporting
confidence: 86%
“…Usually experimental setups have employed large probe molecules able to characterize the interfacial region and to study solvation dynamics in the water pool, 5 although recent works have been focussed directly on the water properties by means of ultrafast infrared (IR) spectroscopy. [6][7][8] In most of the reported studies of aqueous reverse micelles, at least two classes of water molecules are considered: (i) those located nearby surfactant groups and, eventually, counter-ions, which are particularly affected by confinement effects and (ii) water molecules residing in the internal part of the micellar pool, which receive a milder influence of the micellar interface. It has been observed that water structure exhibits important modifications compared to that of the bulk liquid-more notably for interfacial molecules and for small micellar sizes-whereas water dynamics is much less affected.…”
Section: Introductionmentioning
confidence: 99%
“…40,41,81,82 Isotopic dilution leads to cancelation of both inter-and intramolecular couplings between OH (or OD) oscillators. In this case, transient anisotropy experiments on an OH/OD oscillator would provide information explicitly on the orientational dynamics of water molecules.…”
Section: Methodsmentioning
confidence: 99%
“…For example, vesicular structures containing mineral precursors are involved in bone development and sea urchin spiculogenesis (Mahamid et al 2011;Vidavsky et al 2014). Although the effects of macromolecule-or vesicle-based confinement at different length scales on mineralization are not completely clear, some possible explanations for the distinct nucleation behavior are (1) a confinement size-dependent interplay between homogenous and heterogeneous nucleation (Woo et al 2007), (2) critical size constraints corresponding to crystal nuclei (or ion-associates) and related polymorph selectivity (Ha et al 2004), and (3) size constraint-driven thermodynamic crossovers in phase stability (Hamilton et al 2008;Navrotsky 2004;Raiteri and Gale 2010), as well as distinct solvent dynamics and physicochemical conditions in restricted environments and the bulk solvent (Brubach et al 2001;Moilanen et al 2007;. Taken together, biomacromolecular crowding conditions as well as the interfacial aspects and size regime of confinement appear evolutionarily optimized for modulating the nucleation regime including associated phase transition events.…”
Section: Crowded Solutions and Confinement: Impact On Nucleationmentioning
confidence: 99%